Redox-responsive organometallic hydrogels for in situ metal nanoparticle synthesis. Issue 4 (5th November 2014) - Zoetebier, B.; Hempenius, M. A.; Vancso, G. J.
Abstract : A hydrogel composed of poly(ferrocenylsilane) polyanion and poly(ethylene glycol) chains was used to form relatively well-defined, unaggregated Pd(0) nanoparticles (8.2 ± 2.2 nm) from K2 PdCl4 salts. Abstract : A new class of redox active hydrogels composed of poly(ferrocenylsilane) polyanion and poly(ethylene glycol) chains was assembled, using a copper-free azide–alkyne Huisgen cycloaddition reaction. These organometallic hydrogels displayed reversible collapse and reswelling upon chemical oxidation and reduction, respectively, and formed relatively well-defined, unaggregated Pd(0) nanoparticles (8.2 ± 2.2 nm) from K2 PdCl4 salts.